Exploring English Education Students’ Difficulties in Forming Passive Voice Constructions - Munawir, Munawir; Sunubi, Abdul Haris; Said, Dian Riani (Langkawi: Journal of The Association for Arabic and English, 2025)
This study examines the specific challenges Indonesian EFL students encounter when constructing Passive Voice sentences, an area where structural differences between Indonesian and English often lead to systematic errors. The research focuses on identifying the most difficult tense in passive transformation, analyzing dominant error types, and explaining the linguistic factors underlying these errors. Using a descriptive quantitative design, data were collected from 35 students of the English Education Program at IAIN Parepare through a grammar test and a diagnostic questionnaire. The results show that the Simple Past Tense presented the greatest difficulty, indicating learners’ challenges in applying tense markers absent in Indonesian. Misordering emerged as the most frequent error type (57.81%), reflecting limited syntactic awareness and confusion in determining subject-object positions during active-to-passive transformation. Other error types included Selection, Omission, and Addition, each revealing gaps in students’ understanding of participle formation, auxiliary verb usage, and sentence structure. These patterns suggest that L1 interference and insufficient mastery of morphological forms significantly affect learners’ accuracy. The study underscores the need for targeted instructional support, particularly explicit tense-focused instruction and guided practice in sentence transformation. Strengthening learners’ syntactic awareness and verb-form recognition is essential for improving their proficiency in constructing Passive Voice structures